1963
DOI: 10.1182/blood.v21.5.546.546
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Amino Acids on Iron Absorption

Abstract: A series of experiments were devised to determine the effect of various amino acids upon the absorption of iron from the gastrointestinal tract. This was done by introducing single amino acids and Fe59 into isolated loops of small intestine and measuring the serum for radioactivity and the uptake of Fe59 by the liver. It was found that under the conditions of the experiments all of the amino acids studied effected an increase in the serum iron and iron deposition in the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1966
1966
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…It is postulated that in a medium of low pH, food iron is dissolved and ionized and that if the low pH is maintained then the formation of insoluble iron complexes is delayed. The effect of gastric secretion could equally well be due to pepsin which would promote the digestion of iron-containing foods and also increase the concentration of free amino acids in the gut which themselves may stimulate absorption (Kroe, Kinney, Kaufman and Klavins, 1963). The role of acid may be merely to provide a suitable pH for peptic activity.…”
mentioning
confidence: 99%
“…It is postulated that in a medium of low pH, food iron is dissolved and ionized and that if the low pH is maintained then the formation of insoluble iron complexes is delayed. The effect of gastric secretion could equally well be due to pepsin which would promote the digestion of iron-containing foods and also increase the concentration of free amino acids in the gut which themselves may stimulate absorption (Kroe, Kinney, Kaufman and Klavins, 1963). The role of acid may be merely to provide a suitable pH for peptic activity.…”
mentioning
confidence: 99%
“…The F did not contain any calcium, magnesium or phosphate salts which may inhibit iron absorption. Furthermore, the lysine and histidine contained in the F also improve the iron bioavailability [28]. The composition is shown in Table 3.…”
Section: Product Preparationmentioning
confidence: 99%
“…Organic ligands can facilitate the transport of trace elements across biological membranes. Accordingly, the absorption of Fe, Cu or Zn in vivo is improved by the intake of appropriate complexes or amino acid supplements (KROE et al 1963, KIRCH-GESSNER and GRASSMANN 1970, VAN CAMPEN 1972, SCHWARZ andKIRCHGESSNER 1975 [461). In vitro studies using everted intestinal sacs from rats given normal zinc supply showed that among a number of amino acids tested, cysteine and histidine a t high molar excess compared to zinc greatly enhanced the intestinal Zn uptake (FORTH et al 1974) and, yet more so, the Zn transfer M + S (FORTH et al 1974, KIKCHGESSNER andSCHWARZ 1975 [46]).…”
Section: 2 Zn Compoundsmentioning
confidence: 99%